"Off the straight path" : illicit sex, law, and community in Ottoman Aleppo - Semerdjian, Elyse (Gender, culture, and politics in the Middle East., 2008)
"The legal treatment of sexual behavior is a subject that receives little scholarly attention in the field of Middle East women's studies. Important questions about the relationship between sexuality and the law and about the societies enforcing that relationship are rarely addressed in the current literature. Elyse Semerdjian's "Off the Straight Path" takes a bold step toward filling that gap, offering a fascinating look at the historical progression of Islamic law's treatment of illicit sex. Semerdjian provides a comprehensive review of the concept of zina, sexual indiscretion, exploring the diverse interpretation of zina crime as presented in a variety of sources from the Quran and hadith to legal literature. She then delves into the history of legal responses to zina within the specific community of Aleppo, Syria. Drawing on a wealth of shari 'a court records, Semerdjian brings to life Syrian society during the Ottoman period. With vivid detail, she describes specific women's lives and experiences as their cases are presented before the court. Semerdjian argues that the actual treatment of zina crimes in the courts differs substantially from sentences prescribed by codifed Islamic jurisprudence. In contrast to the violent corporal punishments dictated in the Islamic legal code, the courts often punished crimes of sexual indiscretion with nonviolent sentences, such as removal from the community. Employing exceptional insight, "Off the Straight Path" presents a powerful challenge to the traditional view of Islamic law, enabling a richer understanding of Islamic society."--Jacket